3D Printing of Aniline Tetramer‐Grafted‐Polyethylenimine and Pluronic F127 Composites for Electroactive Scaffolds. Issue 4 (3rd January 2017) - Dong, Shi‐Lei; Han, Lu; Du, Cai‐Xia; Wang, Xiao‐Yu; Li, Lu‐Hai; Wei, Yen
Abstract : Electroactive hydrogel scaffolds are fabricated by the 3D‐printing technique using composites of 30% Pluronic F127 and aniline tetramer‐grafted‐polyethylenimine (AT‐PEI) copolymers with various contents from 2.5% to 10%. The synthesized AT‐PEI copolymers can self‐assemble into nanoparticles with the diameter of ≈50 nm and display excellent electroactivity due to AT conjugation. The copolymers are then homogeneously distributed into 30% Pluronic F127 solution by virtue of the thermosensitivity of F127, denoted as F/AT‐PEI composites. Macroscopic photographs of latticed scaffolds elucidate their excellent printability of F/AT‐PEI hydrogels for the 3D‐printing technique. The conductivities of the printed F/AT‐PEI scaffolds are all higher than 2.0 × 10 −3 S cm −1, which are significantly improved compared with that of F127 scaffold with only 0.94 × 10 −3 S cm −1 . Thus, the F/AT‐PEI scaffolds can be considered as candidates for application in electrical stimulation of tissue regeneration such as repair of muscle and cardiac nerve tissue. Abstract : A conductive aniline tetramer (AT) is grafted to polyethylenimine (PEI), i.e., AT‐PEI copolymer, which can self‐assemble into micelle‐like nanostructures. Electroactive scaffolds are fabricated using the composites of Pluronic F127 and AT‐PEI nanoparticles. The conductivities of the 3D‐printed scaffolds are detected by a 3D self‐made apparatus.